Effect of Financial Literation and Financing-Effectivity toward the Growth of Small Enterprises: Case Study in Bank Syariah Mandiri, Majalengka - Robiatul Hikmah; Diana Djuwita; Ridwan Widagdo (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Purposes: This study aims to determine the effect partially and simultaneously between financial literacy and financing effectiveness on business development in Micro Warung financing in Bank Syariah Mandiri Majalengka Branch.Design/Methodology/Approach: This study uses a type of quantitative research. The number of samples is 80 respondents. The technique of collecting data through questionnaires and documentation.Analysis of the data used are research instruments, classical assumptions, multiple linear regression, determinant test, and hypothesis testing, research using SPSS version 20.Findings: The partial test results show that financial literacy variables have a significant positive effect on business development, financing effectiveness has a significant positive effect on development business. The simultaneous test results show that there is a positive and significant influence between financial literacy and financing effectiveness on business development. The effect of financial literacy and financing effectiveness contributes 73.12% to business development.Originality/Value: Main contribution of the article is identified from its issues selected to reach new insight on relationship between financial literation, financing effectivity toward growth of small enterprises. This, exactly, can be a model for previous research on related-issues.